Peripheral nervous system hyperexcitability in VV2 sporadic Creutzfeldt-Jakob disease. Issue 4 (August 2015) - Ong, Charlene J.; Al-Lozi, Muhammad; Cimino, Patrick J.; Bucelli, Robert
Abstract : Summary: Creutzfeldt-Jakob disease (CJD) is a fatal, rapidly progressive neurodegenerative disease. Most cases are sporadic (sCJD). The pathogenesis of sCJD is associated with a conformational change in abnormal prion protein causing widespread neuronal degeneration, and clinical manifestations can be quite protean. Peripheral nerve hyperexcitability syndrome (PNHS) is rarely associated with CJD and is more commonly associated with autoimmune/paraneoplastic syndromes associated with antibodies against the voltage-gated potassium channel complex (VGKC-Abs). Reports of PNHS in CJD are rare. We report 2 patients with progressive cognitive decline in the setting of peripheral nerve hyperexcitability on electrodiagnostic testing. In both patients VGKC-Abs were negative, and autopsy confirmed that both had sCJD, VV2 subtype. While uncommon, it is important to consider sCJD in patients presenting with PNHS and rapidly progressive dementia.